NEO-CULTURE VS. NATURE: AN ECO-FEMINIST PERUSAL OF KAMALA MARKANDAYA’S NECTAR IN A SIEVE - Dr Ashish Kumar Srivastava (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
There has always been augmented academic attention on the myriad issues related to ecology and environment. The issues are the outcomes of commercial and capitalist interests which engage the new tools for the exploitation and capitalization of the Mother Nature and they can be looked at under the canopy of neo-culture in eco-feminism. These tools feed on the parens-patriae (Patriarchal parenting) and the masculine approaches of culture including reductionist science, mal-development, desertification, deforestation, commercial interest, over-exploitation, marketing and cashing the natural resources, etc. This paper endeavors to underline the diverse systems of subjugation and domination against Nature based on the laws of the pre-established patriarchy. It also endeavors to answer the scholastic question – how culture is implicated behind the ecological crisis and the exploitation of Nature?